The effect of load carriage on selected metabolic and perceptual responses of military personnel - Ramabhai, Leena I (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2000)
Taking a multi-disciplinary, integrated approach, the present study sought to examine selected physiological and psycho-physical parameters related to load carriage involving a 12 km march under military conditions. Military constraints hampered, but did not entirely inhibit the secondary aim of the study which concerned the effectiveness of relativising loads in order to normalise responses for all soldiers, irrespective of morphological diversity. Forty three subjects were measured in six groups using a test-retest experimental protocol. They were involved in a rest-broken 12 km march at 4 km.hâ »Â¹ under 40.5 kg absolute total load and under a relative load of 37% of body mass. Heart rates, ratings of perceived exertion (RPE) as well as area and intensity of discomfort were monitored for all subjects. Ten subjects were measured more extensively with regard to physiology using the Metamax, a portable ergospirometry system that provides all the data needed for a complete functional analysis of lung, heart, circulation and metabolic activity. Physiological responses (fc; fb; VÌ‡T; VÌ‡E; VÌ‡Oâ‚‚; EE; VÌ‡COâ‚‚; R; TÂ°) indicated subjects were not severely physically taxed and that the loads imposed constituted a sub-maximal demand. Moreover, there appeared to be a limited cumulative effect over the 3.5 h. Data from the first and third hours were similar, while the significantly higher responses in the second hour reflected the challenge of the undulating terrain encountered during this section of the march. All responses during the Relative load conditions mirrored those of the Absolute load condition but, because the demands were less, the trends occurred at a reduced level. Furthermore, the reduction in inter-individual variability indicates that relativised load carriage tends to stress the soldiers in a more uniform manner. All "local" RPE responses were higher than "central" ratings, suggesting soldiers were in good cardiovascular condition and experienced marginally more strain in the lower limbs. There was increased perceived strain corresponding to the increase in gradient, with little cumulative effect over the three hours. The shoulders and feet were the two regions in which most discomfort was experienced; the shoulders being the worst area in the first hour and the feet being rated the worst after the third hour of marching. This study clearly demonstrates the probability of a significant improvement in mean combat-readiness following loaded marching by showing that, if loads are set at levels commensurate with individual capabilities to carry them without undue strain, unnecessary physical demands experienced by smaller, more gracile soldiers are reduced.
Keywords: Marching -- Physiological aspects; Military art and science; Marching -- Psychological aspects; Lifting and carrying